Pakistan's foreign policy : contemporary developments and dynamics - Ali, Ghulam (Professor) (London ; New York, NY : Routledge, Taylor & Francis Group, 2022)
"This book analyses Pakistan's foreign policy and external relations with a focus on contemporary developments, including the impact of the new government of Prime Minister Imran Khan, the powerful military and the 'middle power' status. Structured in two parts - Foundation and Operationalization - the book provides a broad overview of Pakistan's foreign policy and addresses specific foreign policy choices. Contributors explore issues such as Pakistan's middle power status from a theoretical perspective, Imran Khan's foreign policy, Pakistan's relations with SCO, EU and Pakistan's evolving Indian Ocean strategy. Based on in-depth interviews with Pakistani scholars, politicians and diplomats, the book offers a timely perspective on Pakistan's foreign policy. The book will be of interest to academics working on Pakistan, South Asian Politics, Indian Ocean Studies, Security and Conflict Studies, International Relations and Foreign Policy and Asian Studies"--
Foreign policy of contemporary Pakistan : an overview / Ghulam Ali -- The changing framework of Pakistan's foreign policy under Imran Khan / Syed Ali Zia Jaffery -- Is Pakistan a middle power? / Samee Lashari -- The military and foreign policy in Pakistan : an analysis / Ejaz Hussain -- China-PAkistan : a decade of transformation in diplomacy, 2010-2020 / Gul-i-Hina Shahzad and Rabbiya Kamal -- Afghanistan-Pakistan relations : from uncertainty and confrontation to optimism / Muhammad Azam -- Indian factor in Pakistan's policy towards Afghanistan / Shahzad Akhtar and Arshad Ali -- Geopolitics, the thucydides trap and the China-Pakistan-India trilateral / Rizwan Zeb -- The new conservative parliament in iran and future of Pakistan-Iran relations / Khurram Abbas -- Pakistan-U.S. Relations : is past the prologue? / Rabia Akhtar -- The contours of Pakistan's relations with Russia / Adeela Ahmed -- European Union-Pakistan relations : a critique of strategic engagement plan / Najimdeen Bakare.
Includes bibliographical references and index.
Keywords: Pakistan -- Foreign relations -- 1971-